Hendrik Willem Van Loon papers - Van Loon, Hendrik Willem, 1882-1944.
Chiefly letters from Van Loon to Mae Jurow concerning personal matters (1933-1941). Includes envelopes and postcards illustrated with pen and watercolor by Van Loon and several newspaper clippings.
Author, historian, illustrator, and journalist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Jurow, Mae -- Correspondence; Pen drawing; Watercolor painting; Authors; Historians; Illustrators; Journalists